From lucid dreaming to pure consciousness: a conceptual framework for the OBE, UFO abduction and NDE experiences - Gackenbach, Jayne (My University, 1989)
In order to gain a theoretical understanding of the lucid dream, out-of-body experience (OBE), unidentified flying object abduction experience (UFO), and near-death experience (NDE) it is necessary, as William James, author of the 1902 classic The Varieties of Religious Experience, emphasized, to place things in their series. That is, identify the similarities and differences between experiences in order to understand their nature. The goal of such an inquiry is to identify a common state from which they derive and/or common mechanisms or structures. In this paper lucid dreaming will be framed with the apparently different but related phenomenon of three of the cases presented earlier in this issue of Lucidity Letter (the OBEs of Father X, the UFO abduction described by Felicia Payne and the NDE of Mark Block). A fourth case from this issue, the witnessing experiences of Anja Savolainen, is also relevant later in this discussion. The most obvious set of experiences which lucid dreaming should be considered alongside of are all other dreams, from the mundane true-to-daily-life to the highly bizarre, archetypal, life changing sleep experiences. These comparisons are considered at length elsewhere (Gackenbach, 1988; Gackenbach & Bosveld, in press). Essentially lucid dreams, at the lowest level of consciousness in sleep, are dreams with few content differences from the nonlucid variety. However, I (Gackenbach. in press; Gackenbach & Bosveld, in press), as well as others (Alexander, 1987), have argued that entry level lucidity is only the beginning of the development of consciousness in sleep.
Keywords: lucid dream; out of body experience; OBE; UFO; near death experience; NDE; William James; The Varieties of Religious Experience; Lucidity Letter; Anja Savolainen